The Effects of Spread-Spectrum Techniques in Mitigating Conducted EMI to LED Luminance - Mohammad Yanuar Hariyawan; Risanuri Hidayat; Eka Firmansyah (Institute of Advanced Engineering and Science, 2016)
Rapid voltage and current changes in recently ubiquitous LED driver have a potency to interfere other devices. Solutions with special converter design, component design, EMI filter, and spread-spectrum techniques have been proposed. Due to cost-size-weight constraints, spread-spectrum technique seems a potential candidate in alleviating EMI problem in LED application. In this paper, the effectiveness of conducted EMI suppression performance of the spread-spectrum technique is evaluated. Spread-spectrum techniques applied by giving disturbance to the system LED driver with 3 profile signals, filtered square, triangular, and sine disturbance signal to the switching pattern of a buck LED driver. From the test results, 472.5 kHz triangular and 525 kHz sine signal can reduce EMI about 42 dBuV whilethe filtered square signal can reduce EMI 40.70 dBuV compare with fundamental constantfrequency reference 669 kHz. The average reduction in the power level of the third signal inthe frequency range of 199 kHz to 925 kHz for 5.154281 dBuV and the filtered square signal can reduce the average power level better than other signal disturbance of 5.852618 dBuV.LED luminance decrease when the spread-spectrum technique is applied to the system about 2814 lux.